Prevalence and risk factors for postpartum anemia - Pratiwi, Ika Ratna; Santoso, Sabar; Wahyuningsih, Heni Puji (Jurnal Kesehatan Ibu dan Anak, 2018)
Anemia is a major global health problem, especially in developing countries, the prevalence of postpartum anemia is in the range of 50-80%. SDKI (2015) claimed the prevalence of anemia in Kulon Progo were 49% and prevalence of adolescent anemia were 29,95%.  The prevalence of postpartum anemia has not been studied as extensively as pregnancy anemia. To assess the factors related of postpartum anemia in working area of basic health Wates. Method with analitic observational research type was used in the research. Subject of this research were postpartum mothers wich include in this research, with consecutive sampling technique. A chi-square and a multivariate logistic regression linear model was apllied to analize the factors of postpartum anemia. 60% of mother had postpartum anemia. The risk factors of postpartum anemia were pregnancy anemia (RR:2,195;95%CI:1,369-3,518), maternal age (RR:1,894;95%CI:1,361-3,171), parity (RR:2,000;95%CI:1,020-3,922), type of birth (RR:2,195;95%CI:1,369-3,518), birth weight (RR:1,974;95%CI:1,281-3,044). The most strongly factors with postpartum anemia were pregnancy anemia and type of birth.  Factors relating of postpartum anemia were pregnancy anemia, maternal age, parity, type of birth, and birth weight. The dominants factors were pregnancy anemia and type of birth. Health servicer should early screening to mother with factors of postpartum anemia to avoid postpartum anemia.